2021
DOI: 10.1038/s41598-021-01747-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat generation/absorption and stagnation point on polystyrene–TiO2/H2O hybrid nanofluid flow

Abstract: This article focuses on hybrid nanofluid flow induced by stretched surface. The present context covers stagnation point flow of a hybrid nanofluid with the effect of heat generation/absorption. Currently most famous class of nanofluids is Hybrid nanofluid. It contains polystyrene and titanium oxide as a nanoparticles and water as a base fluid. First time attributes of heat transfer are evaluated by utilizing polystyrene–TiO2/H2O hybrid nanofluid with heat generation/absorption. Partial differential equations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Masood et al [34] discussed about the characteristics of heat generation/absorption over the polystyrene (TiO2/H2O) hybrid nanofluid flow. In their work they found out about the extraordinary enhancement in thermal conductivity of the hybrid nanofluids as compared to just ordinary nanofluids and hence concluded that they partake immeasurable uses in engineering, paints, home, industry, food colorants, ceramics, pharmaceuticals, paper production, in cancer treatment, fabrics, cosmetics, soaps, automotive industry as well as food packaging.…”
Section: Introductionmentioning
confidence: 99%
“…Masood et al [34] discussed about the characteristics of heat generation/absorption over the polystyrene (TiO2/H2O) hybrid nanofluid flow. In their work they found out about the extraordinary enhancement in thermal conductivity of the hybrid nanofluids as compared to just ordinary nanofluids and hence concluded that they partake immeasurable uses in engineering, paints, home, industry, food colorants, ceramics, pharmaceuticals, paper production, in cancer treatment, fabrics, cosmetics, soaps, automotive industry as well as food packaging.…”
Section: Introductionmentioning
confidence: 99%
“…They remarked that the electric field directly influences the temperature profile. In recent years, Hassan 20 , Hussain 21 , Sheikholeslami 22 , Masood and Farooq 23 and Masood 24 have explored hybrid nanofluid in the presence of different body forces.…”
Section: Introductionmentioning
confidence: 99%
“…Different physical phenomenon, ranging from gravitation system to fluid dynamics, are governed by nonlinear partial differential systems (PDEs) and it is difficult to obtain their solutions. Although, similarity technique has been extensively employed in literature [40][41][42][43][44][45][46] to transform the nonlinear PDEs into ODEs, but the technique cannot be used to a significant extent because of some of its limitations. To tackle nonsimilar problems Sparrow and Yu [47] presented the technique of local nonsimialrity.…”
Section: Introductionmentioning
confidence: 99%